The Viaz'ma Catastrophe, 1941 : the Red Army's Disastrous Stand against Operation Typhoon. - Lopukhovsky, Lev (Helion & Company, 2013)
This book describes one of the most terrible tragedies of the Second World War and the events preceding it. The horrible miscalculations made by the Stavka of the Soviet Supreme High Command and the Front commands led in October 1941 to the deaths and imprisonment of hundreds of thousands of their own people. Until recently, the magnitude of the defeats suffered by the Red Army at Viaz'ma and Briansk were simply kept hushed up. For the first time, in this book a full picture of the combat operations that led to this tragedy are laid out in detail, using previously unknown or little-used docume.